Dukungan Mucikari dalam Penggunaan Kondom pada Wanita Pekerja Seks Di Lokalisasi Batursari Batangan Kabupaten Pati - Supriyanto, Supriyanto; Cahyo, Kusyogo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
The Pimp give support to FSWs in used condom for prevent STDS and HIV/AIDS inBatursari Brothel Batangan District Pati; Regular checking of health to FSWs show STDSin Batursari brothel average 95% that is indicator condom used in this Brothel is very lowed.Should be The Pimp give support to FSWs in used condom for prevent STDS and HIV/AIDS.Aim of this study was to identification pimp practice with give support condom use to FSWfor prevent HIV/AIDS in Batursari Brothel Batangan District Pati. This research was adescriptive study with qualitative approach. Pimp respondent included 8 people, fortriangulation included 8 FSWs and 8 FSWs customers. This research showed that Pimpsknowledge of HIV/AIDS still low and knowledge of condom used function is good, pimpsattitude to condom used is support and agree, Pimp practiced for supported condom use toFSWs have advice and remembered to FSW, Condom supply in brothel decreased, informationof media about condom in brothel is decreased, have been supported from peer group, havebeen supported health officer and have been supported the lead of Gajah Asri foundation.Â